Avaliação da assistência pré-natal : em foco a estrutura e o processo assistencial - Arantes, Rayssa Basilio (2014)
ABSTRACT: This study aimed to evaluate the quality of prenatal care provided in the Family Health Strategy (FHS) in the city of Cuiabá, Mato Grosso, based on the Donabediano model. This is a research quality assessment in health (normative evaluation) of quantitative approach. This research was implemented at two different times, using different methods and instruments. Time 1 structure approach and time 2 focused on the process. The data for evaluation of the structure are for the 43 units of the FHS. For description of the units, the data were analyzed using Epi-Info software, version 7.0 through simple descriptive statistical analysis with frequency measures (absolute and relative). After description of the units value judgment was issued, as the dimensions analyzed, being considered: adequate for the one that obtained 10 points, partially adequate of 7 to 9.9 and inadequate down of 6.9 points. For the moment 2 the sample was composed of 350 recent mothers. Process data were collected through survey and transcription of information contained on the cards of the pregnant women. To evaluate this process the prenatal care was focused as regards to the assessment of the early access and the adequacy of the number of queries and also the association of adequacy of prenatal care for these two indicators with variables involved in this process. Descriptive analyses were performed, bivariate and multiple via the Epi-Info version 7.0 programs and Stata version 11.0. The project was submitted to the Research Ethics Committee of the Hospital University Julius Muller, with final approval nº 206,839 CEP-HUJM/2013. The results of the evaluation of the structure showed that the units were partially suitable for physical resources and equipment with proportions of 90.8% and 86.0% respectively. In relation to the assessment of the assistance process, it was found that 60.3% of recent mothers had prenatal care categorized as appropriate. Variables: the regional unit, education, household income, access to first appointment, professional who held consultations and examination of the breasts remained statistically significant association with the adequacy of prenatal care. With the exposed family health units of Cuiabá-MT are still deficient in several respects, hindering the provision of quality services for prenatal care. The care process evaluation highlighted the need conducting certain procedures specified in ministerial proposals, as well as the importance of providing greater visibility to social inequalities.